Acoustic source localization using a polyhedral microphone array and an improved generalized cross-correlation technique. (6th January 2017) - Padois, Thomas; Sgard, Franck; Doutres, Olivier; Berry, Alain
Abstract: Millions of workers are exposed to excessive noise levels each day. Acoustic solutions have to be developed to protect workers from hearing loss. The first step of an acoustic diagnosis is the source localization which can be performed with a microphone array. Spherical microphone arrays can be used to detect the acoustic source positions in a workplace. In this study, a spherical microphone array, with polyhedral discretization, is proposed and compared with a spherical array with a slightly different geometry. The generalized cross-correlation technique is used to detect the source positions. Moreover, two criteria are introduced to improve the noise source map. The first is based on the geometric properties of the microphone array and the scan zone whereas the second is based on the energy of the spatial likelihood function. Numerical data are used to provide a systematic comparison of both geometries and criteria. Finally, experiments in a reverberant room reveal that the polyhedral microphone array associated with both criteria provides the best noise source map.